Identification of non-recurrent submicroscopic genome imbalances: the advantage of genome-wide microarrays over targeted approaches. - Koolen, D; Sistermans, E; Nilessen, W; Knight, S; Regan, R; Liu, Y; Kooy, R; Rooms, L; Romano, C; Fichera, M; Schinzel, A; Baumer, A; et al. (2008)
Genome-wide analysis of DNA copy-number changes using microarray-based technologies has enabled the detection of de novo cryptic chromosome imbalances in approximately 10% of individuals with mental retardation. So far, the majority of these submicroscopic microdeletions/duplications appear to be unique, hampering clinical interpretation and genetic counselling. We hypothesised that the genomic regions involved in these de novo submicroscopic aberrations would be candidates for recurrent copy-number changes in individuals with mental retardation. To test this hypothesis, we used multiplex ligation-dependent probe amplification (MLPA) to screen for copy number changes at eight genomic candidate regions in a European cohort of 710 individuals with idiopathic mental retardation. By doing so, we failed to detect additional submicroscopic rearrangements, indicating that the anomalies tested are non-recurrent in this cohort of patients. The break points flanking the candidate regions did not contain low copy repeats and/or sequence similarities, thus providing an explanation for its non-recurrent nature. On the basis of these data, we propose that the use of genome-wide microarrays is indicated when testing for copy-number changes in individuals with idiopathic mental retardation.